1990
DOI: 10.1111/j.1365-2958.1990.tb00618.x
|View full text |Cite
|
Sign up to set email alerts
|

The life‐cycle proteins RodA of Escherichia coli and SpoVE of Bacillus subtilis have very similar primary structures

Abstract: Comparison of the predicted amino acid sequence of the cell-cycle RodA protein with the National Research Foundation protein sequence database shows that the 370-amino-acid RodA, a protein that is essential for wall elongation in Escherichia coli and maintenance of the rod shape of the cell, is highly analogous, in terms of primary structure, with the Bacillus subtilis SpoVE protein involved in stage V of sporulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…A similar result was obtained for the B. subtilis rodC operon (6). Recently, it was found that the spoVE gene product is homologous to the newly identified E. coli ftsW gene product, in which mutations induce filamentous cell growth at the nonpermissive temperature, and to the newly sequenced E. coli rodA gene product (7,10). These results suggest that SpoVE or the succeeding gene product MurG (15) plays an essential role not only during sporulation but also during vegetative growth.…”
Section: Discussionsupporting
confidence: 74%
“…A similar result was obtained for the B. subtilis rodC operon (6). Recently, it was found that the spoVE gene product is homologous to the newly identified E. coli ftsW gene product, in which mutations induce filamentous cell growth at the nonpermissive temperature, and to the newly sequenced E. coli rodA gene product (7,10). These results suggest that SpoVE or the succeeding gene product MurG (15) plays an essential role not only during sporulation but also during vegetative growth.…”
Section: Discussionsupporting
confidence: 74%
“…Fortunately, a third SEDS family member functions during the nonessential process of sporulation in Bacillus subtilis (18,20). Bacterial endospores can survive extremes of heat and desiccation, largely because of the presence of the spore cortex.…”
mentioning
confidence: 99%
“…For example, inactivation of FtsI delays Z-ring assembly and reduces the total number of rings per unit cell mass by about twofold compared to an unperturbed population of cells (34). Even inactivation of FtsA or ZipA, which localize immediately after FtsZ, has only a modest effect on the number of Z-rings observed per unit mass (2,18,27).FtsW belongs to a large family of polytopic membrane proteins that appear to be present in all bacteria that have a peptidoglycan cell wall (21,22,24). This family has been named SEDS (21) for shape, elongation, division, and sporulation.…”
mentioning
confidence: 99%